A comparative study of oil palm and Japanese beech on their fractionation and characterization as treated by supercritical water - Varman, M.; Saka, S. (Springer Netherlands, 2011)
Supercritical water treatment (380°C/100 MPa/ 8 s) was applied to extractive-free oil palm trunk and sapwood portion of Japanese beech and their fractionated products were comparatively characterized, for water-soluble portion and water-insoluble portion composed of methanol-soluble portion and methanol-insoluble residue. As a result, the water-soluble portion was determined to be composed of carbohydrate-derived products such as organic acids, sugar decomposed products and lignin- derived products, etc. for both species. The oil palm, however, shows higher yield of organic acids (12.9%) and lignin-derived products (12.2%) compared to Japanese beech, in which organic acids were 4.7% in yield and lignin-derived products 9.8%. The methanol-soluble portion was, on the other hand, mainly composed of lignin-derived products, and in oil palm, these lignin-derived products consisted of both syringyl and guaiacyl-type similar to Japanese beech. The methanol-insoluble residue, was also mainly composed of lignin to be 99.2% in its content in the oil palm, compared to Japanese beech 93.7%. Moreover, the phenolic hydroxyl content deter- mined by aminolysis method was higher in oil palm (36.5 PhOH/100C9) compared to Japanese beech (16.9 PhOH/100C9). Furthermore, an alkaline nitrobenzene oxidation analysis indicated that, the methanol-insoluble residue of the oil palm was less in oxidation products whereas in Japanese beech nitrobenzene oxidation products completely diminished. These lines of evidence suggest that methanol-insoluble residue is composed of lignin with more condensed-type of linkages with high phenolic hydroxyl groups. In addition, the water-soluble portion could be utilized for organic acid production, whereas the methanol-soluble portion and its insoluble residue for phenolic chemical production, with oil palm showing higher potential compared to Japanese beech.